The Influence of Leadership, Training, and Motivation on Employee Performance with Competence as an Intervening Variable at the Bangun Insan Mandiri Education Foundation in Medan - Sodik, Muhammad Amir; Anwar, Yohny (Riwayat: Educational Journal of History and Humanities, 2025)
https://jurnal.usk.ac.id/riwayatThis paper aims to analyze the influence of leadership, training, and motivation on employee performance with competence as an intervening variable at the Bangun Insan Mandiri Education Foundation in Medan. This study employs a quantitative approach using a survey method, with data collected through questionnaires distributed to all employees of the foundation. Data analysis was conducted using Structural Equation Modeling (SEM) to test the direct and indirect relationships among the variables. The results indicate that leadership, training, and motivation have a positive and significant influence on employee competencies. Competencies were also found to have a significant influence on employee performance. Additionally, competence mediates the relationship between leadership, training, and motivation toward performance. These findings indicate that enhancing employee competence is key to strengthening the positive impact of leadership, training, and motivation on performance. The implications of this study suggest that foundation management should continue to develop effective leadership, relevant training programs, and appropriate motivation strategies to improve employee competence and overall performance.